Comparison of Palliative Fractionated Radiotherapy to Thorax in Non-small Cell Lung Carcinoma: A Prospective Comparative Study - Mayur Khandelwal; Divya Sharma; Priya Tawri; Shruti Paliwal; Neeti Sharma; Shankar Lal Jakhar (Asian Pacific Journal of Cancer Care, 2024)
Background: Most patients of lung carcinoma come into the OPD with advance disease and with moderate to severe symptoms. Palliative Radiotherapy to chest can relieve symptoms arising due to intrathoracic pathology. Timing and fractionation schedule is very important for symptomatic relief and response. Time to come the effect of RT is 3 months. The aim of this study is to investigate survival after PTR and evaluate symptomatic relief and adverse effects of RT. Methods: Patients with non-small-cell lung cancer (NSCLC) planned for PTR in the period of January 2022 to October 2022 at ATRCTRI Bikaner (Rajasthan). We noted pathology, tumor, node, and metastasis (TNM) classification of malignant tumors, stage, indication, starting date, schedule for PTR, completed yes/no, performance status (PS) and time of death. Results: Out of total 86 patients 12 patients did not complete RT. Rest 74 patients who received PTR included in the study, 30 patients (40%) died within 30 days and 15 patients died within 3 months of treatment. Only 20 patients remained alive at 6 months. More Symptomatic relief seen with 20 Gy in 5 fractions. More Survival seen with PS 1-2 and 30Gy/10fraction. Dyspnea, hemoptysis, and SVC syndrome were the most frequent indications for PTR in our study. Almost every patient noted for >1 indication. Fractionated schedule 30Gy/10F used more frequently in good PS patients. Conclusions: Our study shows that a significant number of patients who received PTR died before they could achieve optimal effect of the treatment. PS and histology were significant prognostic factors favoring PS 1-2 and squamous cell carcinoma. Based on our study, we suggest that patients with PS 1-2 should be considered for fractionated PTR whereas patients with PS ≥ 2 should be considered for comparatively shorter fractionation size or best supportive palliative care.